The influences of accessibility, information technology and social capital on coastal development in Indonesia: The mediating role of port development. (15th May 2022) - Syafiq, Muhammad; Sirojuzilam,; Badaruddin,; Purwoko, Agus
Abstract: Port as a transportation terminal plays a significant role in developing coastal areas. Some of the factors supporting its development in coastal areas are accessibility, information technology, and social capital. Therefore, this research analyzes the influence of accessibility, information technology, and social capital on the development of the Bagan Asahan Port and its surrounding coastal areas in the Asahan Regency. This is a quantitative research with data collected from 392 respondents through a questionnaire and analyzed using Structural Equation Modeling. The results showed that accessibility and information technology had no significant effect on port and coastal area development. Conversely, social capital significantly affected the port area with no significant impact on coastal development. Subsequently, port development also has a substantial effect on developing coastal areas with mediating influence on social capital. Numerous implications and recommendations for future research are then discussed and presented. Highlights: Influences of accessibility, information technology and social capital on port development and coastal development. New instruments for accessibility, information technology, social capital, port development and coastal development. Role of port development in mediating social capital influence on coastal development.